Use of fenugreek plant Trigonella foenum-graecum L. and spraying with melatonin and glutathione in treating soils contaminated with petroleum hydrocarbons - Hussian, Khtam Ali; Athfua, Qasim Jassim (University of Thi-Qar Journal of agricultural research, 2025)
Abstract: The experiment was conducted during the 2023-2024 growing season in the College of Education - Al-Qurna / University of Basrah fields. To treat soils contaminated with crude oil in Basrah Governorate and to study the effect of oxidative stress of crude oil and antioxidants melatonin and glutathione on some vegetative growth traits. The study examined the effects of two factors: soil contamination with crude oil at concentrations of 0, 2, 4, and 6 g/kg, and three spray treatments – water (control), melatonin, and glutathione at concentrations of 100 and 200 mg/L. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replicates, and the averages were compared at a significance level of 0.05. Following the analysis of experimental measurements taken after plant growth, the results indicated that plants exhibited tolerance and resistance to varying crude oil concentrations. However, as crude oil levels increased, vegetative growth indicators, including plant height, fresh weight, and dry weight, showed a noticeable decline. This highlights the negative impact of higher crude oil concentrations on plant growth and development. The results of external treatment with melatonin and glutathione were an increase in the above characteristics, as the control plants were sprayed with melatonin and glutathione at a concentration of 200 mg. L-1 gave the highest plant height and fresh and dry weights, reaching 46.00 and 50.33 cm, 7.39 and 6.63 g, and 1.08 and 1.62 g, respectively. As for the content of total hydrocarbons TPHs in the root system and remaining in the soil after planting for plants, it increased with increasing concentrations of crude oil in the soil. The percentage of total treatment with spraying plants with melatonin at a concentration of 200 mg. L-1 reached 95.24, 95.33, 87.78, and 79.09% respectively, and sprayed with glutathione at a concentration of 200 mg. L-1 reached 95.52, 96.13, 86.95 and 80.10%.